Ground Motion Characteristics of the 2015 Gorkha Earthquake, Survey of Damage to Stone Masonry Structures and Structural Field Tests - Parajuli, Rishi Ram; Kiyono, Junji (Frontiers in Built Environment, 2015)
On April 25, 2015, a M7.8 earthquake rattled central Nepal; ground motion recorded in Kantipath, Kathmandu, 76.86 km east of the epicenter suggested that the low frequency component was dominant. We consider data from eight aftershocks following the Gorkha earthquake and analyze ground motion characteristics; we found that most of the ground motion records are dominated by low frequencies for events with a moment magnitude greater than 6. The Gorkha earthquake devastated hundreds of thousands of structures. In the countryside, and especially in rural mountainous areas, most of the buildings that collapsed were stone masonry constructions. Detailed damage assessments of stone masonry buildings in Harmi Gorkha had done, with an epicentral distance of about 17 km. Structures were categorized as large, medium and small depending on their plinth area size and number of stories. Most of the structures in the area were damaged; interestingly, all ridge-line structures were heavily damaged. Moreover, Schmidt hammer tests were undertaken to determine the compressive strength of stone masonry, brick masonry with mud mortar for normal buildings and historical monuments. The compressive strengths of stone and brick masonry were found to be 12.38 and 18.75 MPa, respectively. Historical structures constructed with special bricks had a compressive strength of 29.50 MPa. Pullout tests were also conducted to determine the stone masonry-mud mortar bond strength. The cohesive strength of mud mortar and the coefficient of friction were determined.